2018
DOI: 10.1007/978-1-4939-8709-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Lymphoid Structures Among the World of Noncanonical Ectopic Lymphoid Organizations

Abstract: Tertiary lymphoid structures (TLOs), also known as ectopic lymphoid structures, are associated with chronic infections and inflammatory diseases. Despite their association with pathology, these structures are actually a normal, albeit transient, component of the immune system and facilitate local immune responses that are meant to mitigate inflammation and resolve infection. Many of the mechanisms controlling the formation and function of tertiary lymphoid structures have been identified, in part by experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…In autoimmune diseases and allograft rejection, their presence has been associated with an unfavorable clinical evolution (54)(55)(56)(57)(58), as opposed to the favorable outcome observed in cancers associated with their presence. In local infections, their role and prognostic value are more variable and depend on their location, composition and on the considered pathogen (58,59). Remarkably, the study of TLS in these pathological conditions has provided a better understanding of the events that lead to their neogenesis in specific organs and might give some helpful clues in the field of tumor immunology (57).…”
Section: Learning From Tls Study In Non-tumor Inflammatory Diseases To Better Understand Tls Role In Cancermentioning
confidence: 99%
“…In autoimmune diseases and allograft rejection, their presence has been associated with an unfavorable clinical evolution (54)(55)(56)(57)(58), as opposed to the favorable outcome observed in cancers associated with their presence. In local infections, their role and prognostic value are more variable and depend on their location, composition and on the considered pathogen (58,59). Remarkably, the study of TLS in these pathological conditions has provided a better understanding of the events that lead to their neogenesis in specific organs and might give some helpful clues in the field of tumor immunology (57).…”
Section: Learning From Tls Study In Non-tumor Inflammatory Diseases To Better Understand Tls Role In Cancermentioning
confidence: 99%
“…However, like pDCs, fDCs may be present in inflammatory conditions and chronic infections of non‐lymphoid tissues 13,33 . Our study only found CD21 in two intraoral mucosa (IM) samples, and the control was entirely negative.…”
Section: Discussionmentioning
confidence: 50%
“…12 However, like pDCs, fDCs may be present in inflammatory conditions and chronic infections of non-lymphoid tissues. 13,33 Our study only found CD21 in two intraoral mucosa (IM) samples, and the control was entirely negative. In some other specimens, intense LP-clustered CD21 immunoexpression was observed, probably corresponding to ectopic lymphoid follicles.…”
Section: Conflict Of Interest Statementmentioning
confidence: 66%
See 1 more Smart Citation
“…A previous study showed that lymphocytes in TLOs overproduce the proinflammatory cytokines under a sustained situation caused an unsolvable inflammation status in the kidney ( 24 ). Additionally, TLOs do not have capsular-like lymph nodes ( 25 ). Thus, the cells and cytokines of TLOs can expand to the renal interstitial part and occupy broad areas of parenchyma in the kidneys, which enforced the inflammation of the kidneys ( 9 ).…”
Section: Discussionmentioning
confidence: 99%